Centaurea baseri (Compositae), a new species from Turkey - Kose, Yavuz Bulent; Alan, Sevim (Phytotaxa, 2013)
Centaurea baseri, a new species from limestone rocks in Emirdağ (Afyon), Central Anatolia, Turkey, is described and illustrated. The new species is compared with the most similar species C. aphrodisea and C. dursunbeyensis (C. sect. Phalolepis), from which it differs in its involucre, basal leaves, achenes, appendages and habit. Diagnostic morphological characters are discussed. Notes are presented on its ecology and conservation status.